PENERAPAN MODEL PEMBELAJARAN KOOPERATIFTIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS IISD NEGERI 010 SILIKUAN HULU KECAMATAN UKUI - Suharni ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The problem in this research is the low student learning outcomes PKn class II SD Negeri 010 Silikuan Hulu, which amounted to 65.33. Based on this, researchers conducted a study with the aim to improve student learning outcomes PKn through the implementation of cooperative learning model type STAD. This research is a class act that is safe to do as much as two cycles consisting of two meetings and a daily test on each cycle. The data collection technique used is the technique of observation activities of teachers and students and learning outcomes PKn tse techniques. The analysis technique used is descriptive analysis. The results showed that the application of cooperative learning model STAD can increase the learning outcomes of students PKn class II. This is supported by: (1) the activities of teachers has increased, in the first cycle of the first meeting obtained a score of 19 or 76.00% in both categories. At the second meeting of the first cycle of activities for teachers to get a score of 21 or 84.00% in both categories. At the first meeting of the second cycle of activity for teachers to get a score of 22 or 88.00% with a very good category. At the second meeting of the second cycle of activity for teachers to get a score of 24 or 96.00% with a very good category. In addition students are also experiencing an increase in activity in the first meeting of the first cycle, the activity of the students obtained a score of 18 or 72.00% in both categories. Activities students obtain a score of 21 or 84.00% in both categories. On the activities of students obtained a score of 23 or 92.00% with a very good category. Activity second meeting students obtained a score of 24 or 96.00% with a very good category; (2) The student learning outcomes in basic score students' average grades increased 65.53 on the first cycle as much as 46.44% to 78.03 with the percentage thoroughly studied 82.14%, increased again in the second cycle as much as 60.70% to 81.96 with the percentage of 96.40% thoroughly studied. In addition completeness of student learning outcomes also improved on the basis of the number of completeness score of students numbering 10 students or 35.70% with category yet complete and the first cycle increased with the number of 23 students or 82.14% with complete categories and the second cycle increases with the number of 27 students or 96.40% with a complete category.